Work Life Balance and Job Satisfaction among Employees in Nepalese Commercial Banks - Pathak, Resham Raj; Chalise, Mahananda; Dangol, Jeetendra (Journal of Business and Social Sciences Research, 2025)
This study attempts to investigate the relationship between work-life balance and job satisfaction among employees working in the Nepalese commercial banks. The study addresses a gap in the literature by exploring various dimensions of work-life balance with a focus on sub-variables such as work family conflict (WFC) and family work conflict (FWC). Applying a cross-sectional research design, the study has surveyed 584 respondents at officer level and other higher-ranking officials using a convenience sampling method. Data were collected through 700 distributed questionnaires across six commercial banks, including both state-owned and non-state-owned institutions. Pearson correlation and multiple regression techniques were applied for quantitative analysis. The findings reveal that both WFC and FWC are negatively associated with job satisfaction. The study provides actionable insights for enhancing work-life balance and improving satisfaction of employee in the Nepalese commercial banks. By addressing work-family conflicts through tailored strategies and supportive policies, organisations can foster a positive work environment for promoting employee well-being that would help assure an organisational success.